Asteroid impact effects and their immediate hazards for human populations. Issue 8 (19th April 2017) - Rumpf, Clemens M.; Lewis, Hugh G.; Atkinson, Peter M.
Abstract: A set of 50, 000 artificial Earth impacting asteroids was used to obtain, for the first time, information about the dominance of individual impact effects such as wind blast, overpressure shock, thermal radiation, cratering, seismic shaking, ejecta deposition, and tsunami for the loss of human life during an impact event for impactor sizes between 15 and 400 m and how the dominance of impact effects changes over size. Information about the dominance of each impact effect can enable disaster managers to plan for the most relevant effects in the event of an asteroid impact. Furthermore, the analysis of average casualty numbers per impactor shows that there is a significant difference in expected loss for airburst and surface impacts and that the average impact over land is an order of magnitude more dangerous than one over water. Key Points: Dominance of impact effects that are generated by asteroid impacts for every impactor diameter in the range of 0‐400 m Average casualty count estimation for impactors in the diameter range of 0‐400 m Impactors over land are an order of magnitude more harmful than over water despite the generation of tsunamis Plain Language Summary: The impacts of 50, 000 asteroids have been simulated all over the Earth, and this analysis gave new insights into the asteroid impact hazard. The expected number of casualties for an impactor of a given size has been determined. Furthermore, it was analyzed which of the resulting impact effects are most dominant for the human population. This research increases our understanding of the asteroid impact hazard and how to prepare to it. A surprising result was that tsunamis are less of a threat than generally assumed in the literature. The analysis is valid for asteroids up to 400 m in diameter, and these asteroids collide with Earth more often than larger asteroids, increasing this research's relevance.